Prescribing of methylphenidate to children and adolescents in South Africa: A pharmacoepidemiological investigation - Ilse Truter (South African Family Practice)
Background: Pharmacoepidemiological studies on ADHD are limited in South Africa. The primary aim was to analyse the prescribing of methylphenidate to patients aged 18 years and younger in the private health care sector.